Enhancing students' pedagogical potential with practice-oriented courses in teacher education universities - Ybyraimzhanov, Kalibek; Zhaxylikova, Kulyay; Koishibaev, Makhambetzhan; Omurzakova, Alfiya; Ayapbergenova, Gulsum (Journal of Education and e-Learning Research, 2023)
The main aim of this study is to evaluate the effectiveness of the course designed by the author, which focuses on practical application, in improving students' pedagogical skills. Furthermore, the research aims to identify the challenges faced by teacher education institutions in this context and examine the mechanisms involved in improving pedagogical capabilities. The evaluation of students' instructional capacity is conducted through the utilization of both quantitative and qualitative methodologies. The Mann-Whitney U-test statistical test was used to confirm that the data conformed to the normal distribution law. The research encompassed a sample of 51 students from Zhetysu University, specifically named after I. Zhansugurov, located in Kazakhstan. The results showed that the conditions for supporting the pedagogical potential of students are not sufficiently created at the university. This demonstrated the necessity of the upcoming tasks, which included the introduction of the author's practice-oriented course and the development of pedagogical environments for the preparation of future educators to enhance their pedagogical potential. Finally, higher education policy experts in Kazakhstan might employ "practice-oriented courses" and pedagogical settings to improve the pedagogical expertise of future educators in pedagogical universities.